Isolation, structural characterization, and hypoglycemic activity of polysaccharides from the stems of Panax ginseng C. A. Meyer - Xu, Weiwei; Zhou, Wei; Sun, Jinfeng; Chen, Weiwei; Wu, Xuanye; Guan, Tong; Zhao, Yilin; Yang, Pengcheng; Hu, Zhengyu; Li, Gao (Frontiers in Sustainable Food Systems, 2024)
The purpose of this study was to obtain polysaccharides from Panax ginseng C. A. Meyer stems (PGSPs), agro-byproducts with development potential, and fully explore the potential value in P. ginseng stems. Two novel polysaccharides firstly from P. ginseng stems (PGSP-1 and PGSP-2) were obtained by water extraction and alcohol precipitation method and column chromatography, and then characterized by FT-IR, HPGPC, HPLC, SEM, TGA, GC-MS and NMR. The results demonstrated that PGSP-1 (Mw=723.83 kDa) and PGSP-2 (Mw=620.48 kDa) were characterized →4)-β-D-Galp-(1→, →6)-α-D-Glcp-(1→ and →2)-α-L-Rhap-(1→ as the skeleton, →4,6)-β-D-Galp-(1→ and →2,6)-α-D-Manp-(1→ as the cross junction, α-L-Araf-(1→ as the terminal unit, and PGSP-1 still contained →4)-β-D-Galp, while PGSP-2 contained →4)-β-D-Xylp-(1→, →3)-β-D-GlcpA-(1→, →4)-β-D-GalpA-(1→ and α-D-Glcp-(1→,with different microstructures and thermal stability. And the results of hypoglycemic activity revealed that both PGSP-1 and PGSP-2 showed excellent inhibitory activity against α-glucosidase and α-amylase, in which PGSP-2 had the better performance.The inhibition kinetics result showed that PGSPs on α-glucosidase and α-amylase were non-competitive type and mixed type inhibition. This study provided a theoretical basis for making full use of and exploiting the economic value of agro-byproducts such as P. ginseng stems and offered a theoretical reference for the effective utilization of PGSP as a functional component to prevent and reduce T2DM.